2007
DOI: 10.1152/japplphysiol.00193.2006
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory impairment in a mouse model of amyotrophic lateral sclerosis

Abstract: Tankersley CG, Haenggeli C, Rothstein JD. Respiratory impairment in a mouse model of amyotrophic lateral sclerosis. J Appl Physiol 102: 926 -932, 2007. First published November 16, 2006; doi:10.1152/japplphysiol.00193.2006.-Amyothrophic lateral sclerosis (ALS) is a progressive, lethal neuromuscular disease that is associated with the degeneration of cortical and spinal motoneurons, leading to atrophy of limb, axial, and respiratory muscles. Patients with ALS invariably develop respiratory muscle weakness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…In this study, respiratory function and diaphragm muscle tension was investigated after female B6SJL-SOD1 G93A mice reached a 40% deficit in forelimb grip strength, or approximately 18 weeks of age. Consistent with prior work [20] respiratory function did not appear to be compromised in B6SJL-SOD1 G93A mice at this stage in their disease progression since breath frequency and tidal volume were not significantly different from age-matched WT mice at room air or when exposed to a 5% hypercapnic challenge (data not shown). Treatment with tirasemtiv did lead to decreased breath frequency and a significant increase in tidal volume (Figure 7A) which are indicative of an effect on diaphragm function.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, respiratory function and diaphragm muscle tension was investigated after female B6SJL-SOD1 G93A mice reached a 40% deficit in forelimb grip strength, or approximately 18 weeks of age. Consistent with prior work [20] respiratory function did not appear to be compromised in B6SJL-SOD1 G93A mice at this stage in their disease progression since breath frequency and tidal volume were not significantly different from age-matched WT mice at room air or when exposed to a 5% hypercapnic challenge (data not shown). Treatment with tirasemtiv did lead to decreased breath frequency and a significant increase in tidal volume (Figure 7A) which are indicative of an effect on diaphragm function.…”
Section: Discussionsupporting
confidence: 89%
“…Growth rates for SOD1-G93A and control mice were similar until a decline began in the affected mice at approximately 95 days of age. Other studies reported differences in body weight between SOD1-G93A and control mice emerging much later, from approximately 98 days to approximately 126 days (Weydt et al, 2003;Tankersley et al, 2007). Here, we observed a consistent significant difference in weight beginning at 108 days of age.…”
Section: Body Weightsupporting
confidence: 87%
“…As H 2 CO 3 dissociates (and CO 2 is expelled by the lungs) H + removal (alkalization) is promoted as H + combines with HCO 3 − . Given these processes, it is not surprising that an increase in breathing frequency, tidal volume, and CO 2 production was found to occur in SOD1 G93A mice several weeks before death (29). Sustained hyperventilation leading to CO 2 depletion within the CNS, however, will initiate vasoconstriction, reduced blood flow, ischemia, and edema (30)-all occurring in the spinal cord of SOD1 G93A mice before motor neuron degeneration (31,32).…”
Section: Discussionmentioning
confidence: 99%